SHUROBASHAT ARCHAEOLOGY AT THE ROOTS OF FERGANA CIVILIZATION - Alisher Axmadjonovich Aloxunov; Tashmatov Bahtiyor Davlataliyevich (Modern American Journals, 2025)
This article analyzes the historical and archaeological significance of the Shurobashat archaeological site located in the Fergana Valley. Excavations conducted between the 1950s and 1990s, along with studies in 1993, revealed that the site comprises three distinct parts, is equipped with strong defensive walls, includes a massive foundation in the citadel (ark), and reflects multiple construction phases. The discovered pottery and construction methods indicate the continuation of Chust–Eylaton cultural traditions and date the initial formation of the site to the first millennium BCE. The article also highlights the strategic location, as well as the economic and political importance of the site. It explores the development of urban culture, its topography, and the potential comparison of Shurobashat with the city of Yu (Yuchen) mentioned in Chinese sources.
Keywords: Shurobashat, Fergana Valley, archaeology, urban culture, Eylaton culture, agriculture, ark, defensive walls, pottery, ancient city, Dawan, city of Yu, Qoradaryo.